Social Support in Determining Coping Strategies Among Adolescents in Urban City: Evidence from Post COVID-19 - Rizkiyani Istifada; Firda Widyasari; Hera Hastuti; Robby Prihadi Aulia Erlando (Professional Health Journal)
Introduction: The process of life has changed in the post-pandemic COVID-19 era, including in the educational setting of schools. This condition has an impact on adolescents who tend to struggle in determining effective coping strategies. Adolescents require a lot of support in resolving their chosen coping strategies.